Body Scrub Kombinasi Cangkang Telur Ayam Horn dan Ekstrak Daun Kenikir Sebagai Brightening Skin - Yunitasari, Risky; Natasya, Leanasta Ina; Poppy, Leony Rayvina; Agustin, Nanda Nelly; Fatika, Diva Aulia Nur; Isnawati, Nafisah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Maintaining beauty is an important aspect for every woman, including appearance and cleanliness of the entire body. One product that supports healthy skin is a body scrub, which can be made using egg shell waste as a scrub and kenikir leaf extract as the active ingredient for a body scrub. Egg shells contain calcium carbonate which is abrasive for exfoliation. Meanwhile, kenikir leaves are rich in antioxidants, vitamins C, A and E which play a role in brightening the skin. The method used is a qualitative and quantitative experimental research method which includes physical evaluation and antioxidant activity testing of body scrub preparations. The aim of this research is to determine the formulation, characteristics and antioxidant activity of a combination of horn chicken (Gallus gallus domesticus) egg shell waste and kenikir (Cosmos caudatus) leaf extract using the DPPH method and to evaluate the physical preparation. The research results showed that the physical evaluation of the body scrub preparation met the requirements and the best antioxidant activity was found in F3 with an IC50 value in the medium category of 111.121.